Taxonomic revisions of Dipterocarpaceae in Kinabalu Park, Kundasang Sabah / Ahmad Fariz Nicholas - Nicholas, Ahmad Fariz (2013)
The total number of Dipterocarpaceae Deposited Specimens Voucher (DSV) in Kinabalu Park is 143. It is categories into 7 genera which are Anisoptera Korth, Dipterocarpus Gaertn.f. Dryobalanops Gaertn.f, Hopea Roxb, Parashores Kurz, Shorea Roxb and Vatica L. There are 45 species and 9 unknown species deposited. The unknown species are H. sp (SNP 1903) which deposited to H. dyeri_F. Heim, S. sp PEK ( KB 266) deposited to S. foxworthyii Symington, S. sp PEK (DA 942) and PEK (AB 608) deposited to S. gibbosa Brandis, S. sp PEK ( AB 607) deposited to P. tomentella (Symington) Meijer, S.sp PEK (MR 319) deposited to S. parvistipulata F .Heim, V. sp (SNP 0163) and (SNP 0457) deposited to V. albiramis Slooten, and V.sp (SAN 94289) deposited to S. laevis Ridl. There are 4 invalid DSV detected. The invalid DSV are H. beccariana Burck (SP 18147) which the characteristics are resemble to H. mengerawan Miq, H. semicunenata Symington (PEK (MR 300)) to S. laevis Ridl, P. malaanonan (Blanco) Merr (SP 18145) to P. tomentella (Symington) Meijer, and S. dasyphylla Foxw (SP 18783) resemble to S. parvistipulata F .Heim. Key dichotomous of Dipterocarpaceae in Kinabalu Park is constructed based on Ashton's field characteristics.